2011
DOI: 10.4061/2011/235926
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Analysis of Breast Tumor Cells

Abstract: An attractive alternative treatment for malignant tumors that are refractive to conventional therapies, such as surgery, radiation, and chemotherapy, is electrical-pulse-mediated drug delivery. Electric field distribution of tissue/tumor is important for effective treatment of tissues. This paper deals with the electric field distribution study of a tissue model using MAXWELL 3D Simulator. Our results indicate that tumor tissue had lower electric field strength compared to normal cells, which makes them suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It was reported that the electric field is decreased if the same protocol is used for tumors, deep seated with a human breast [14]. The tumor tissue had lower electric field strength compared to normal cells [15]. The capacitance or conductance of breast cancer malignancy is 50 times higher than that of normal tissues or benign lesions [15].…”
Section: Results and Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…It was reported that the electric field is decreased if the same protocol is used for tumors, deep seated with a human breast [14]. The tumor tissue had lower electric field strength compared to normal cells [15]. The capacitance or conductance of breast cancer malignancy is 50 times higher than that of normal tissues or benign lesions [15].…”
Section: Results and Analysismentioning
confidence: 97%
“…The tumor tissue had lower electric field strength compared to normal cells [15]. The capacitance or conductance of breast cancer malignancy is 50 times higher than that of normal tissues or benign lesions [15].…”
Section: Results and Analysismentioning
confidence: 99%
“…The efficiency of this approach depends on effective permeabilization of target cells due to exposure of adequate electric field distribution. As per the this technique, a potential difference is induced across the membrane because of the external electric field and thereby establishing a transmembrane voltage (TMV) [6,7]. H. P. Schwan and co-workers came up with the canonical theory of TMV [6].…”
Section: Introductionmentioning
confidence: 98%
“…The various parameters which influence the process of electroporation are electric potential (field intensity), pulse width, number of pulses, types of chemo drug, and size and geometry of the tumor [5][6][7]. In addition, the efficiency of electroporation also depends on the type, size and shape of electrodes.…”
Section: Introductionmentioning
confidence: 99%